(untitled) (Comprehensive Journal of Science, 2025)
This study sets out to investigate the importance of Teaching Practice stage on developing teaching skills. It also, to identify which teaching skills are most developed during the practicum and the challenges they encounter in implementing Teaching Practice. The data of the study was collected through 30 student teachers who are in the practicum experience at Zawia Faculty of Education who were performing teaching practicum during their final semester in public schools. The results of this study indicated that trained teachers are better than untrained and the participants held positive perspectives regarding the importance of Teaching Practice in enhancing their teaching skills. It was recommended that teacher-training courses for teachers should be achieved and student teachers should be encouraged to undergo professional teaching courses and use variety of teaching methods.